Influencing effects and spatiotemporal differentiation of pollutant discharge from industrial wastewater and domestic sewage in China - Zhang, Chen; Liu, Yanxiao; Lan, Ling; You, Yue; Ye, Yuepeng (Frontiers in Environmental Science, 2025)
The driving forces and their spatiotemporal differences of pollutant discharge in 30 provinces in China from 2001 to 2020 were investigated by adopting the logarithmic mean divisia index (LMDI) method, distinguishing between industrial and domestic wastewater pollutant discharge. Our study results show that economic expansion was the dominant driver of chemical oxygen demand (COD) and NH3-N discharge in China, mainly due to the impact of rapid economic development in the developed eastern provinces. The gap among 30 provinces in the contribution related to the driving effects of industrial COD and NH3-N discharge greatly narrowed with time, tending toward the national average. It showed the significant effectiveness of industrial structure adjustment, clean production, and the technology of industrial wastewater treatment across the country. Industrial COD and NH3-N discharge has been reduced to a certain extent. However, with rapid economic growth and urbanization, the domestic sewage treatment volume was still increasing, and the growth rate was faster than that of GDP in some provinces. The technology of many provinces had gradually failed to meet the growing demand for treating domestic sewage pollutants. Consequently, the influencing contributions had significant regional differences among provinces. The governance of the water environment in China should attach importance to technological advances for domestic water conservation and wastewater treatment in the future.